Implementation of Islamic Education Curriculum in Muhammadiyah 3 Basic School Padang Sidempuan - Yusnaldi, Eka; Siregar, Hendri; Damanik, Muhd Hayyanul; Iskandar, Wahyu; Yusuf, Muhammad (SYAMIL: Journal of Islamic Education, 2020)
The curriculum in Islamic education is known as the manhaj or "path" of the educational process in an institutional system. The qualitative research used in this study intends to find out and describe in detail the implementation of the Islamic religious education curriculum (PAI) in Muhammadiyah 3 Padang Sidempuan elementary school which includes how to plan the PAI curriculum at SD Muhammadiyah 3 Padang Sidempuan, how the PAI curriculum is implemented at SD Muhammadiyah 3 Padang Sidempuan and how to evaluate the PAI curriculum at SD Muhammadiyah 3 Padang Sidempuan. The results of this study (1) Planning the PAI Curriculum at SD Muhammadiyah 3 Padang Sidempuan, stated that SD Muhammadiyah 3 Padang Sidempuan held work meetings for PAI curriculum planning and organized technical guidance which aimed to create elaboration of educators in various fields. (2) The implementation of the PAI curriculum at SD Muhammadiyah 3 Padang Sidempuan has so far implemented the PAI curriculum in accordance with the stages that must be taken in the learning process using the development of the 2013 curriculum. (3) Evaluation of the PAI curriculum at SD Muhammadiyah 3 Padangsidimpuan school principals carry out Quality Control and Reporting. Evaluating the obstacles faced by teachers at SD Muhammadiyah 3 Padangsidimpuan. The obstacles that occur are there are still senior teachers who have not been able to teach Islamic Education learning with technology-based media.